2020
DOI: 10.1001/jamapsychiatry.2020.0770
|View full text |Cite
|
Sign up to set email alerts
|

Association of Nondiscrimination Policies With Mental Health Among Gender Minority Individuals

Abstract: In the past decade, many states have implemented policies prohibiting private health insurers from discriminating based on gender identity. Policies banning discrimination have the potential to improve access to care and health outcomes among gender minority (ie, transgender and gender diverse) populations.OBJECTIVE To evaluate whether state-level nondiscrimination policies are associated with suicidality and inpatient mental health hospitalizations among privately insured gender minority individuals. DESIGN, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 25 publications
0
26
1
Order By: Relevance
“…While previous studies found positive outcomes where state-level policies were protective, such as reduced suicidal ideation or attempts [ 10 , 41 , 42 ] or greater utilization of healthcare services [ 43 ], we found either null results or greater odds of discrimination and victimization. The social context in the USA, as viewed through the social ecological model, is an important consideration to interpret these unexpected findings.…”
Section: Discussioncontrasting
confidence: 95%
“…While previous studies found positive outcomes where state-level policies were protective, such as reduced suicidal ideation or attempts [ 10 , 41 , 42 ] or greater utilization of healthcare services [ 43 ], we found either null results or greater odds of discrimination and victimization. The social context in the USA, as viewed through the social ecological model, is an important consideration to interpret these unexpected findings.…”
Section: Discussioncontrasting
confidence: 95%
“…However, transgender identity is not a mental illness, and these elevated rates have been linked to complex trauma, societal stigma, violence, and discrimination (Nuttbrock et al., 2014 ; Peterson et al., 2021 ). In addition, psychiatric symptoms lessen with appropriate gender-affirming medical and surgical care (Aldridge et al., 2020 ; Almazan and Keuroghlian; 2021; Bauer et al., 2015 ; Grannis et al., 2021 ) and with interventions that lessen discrimination and minority stress (Bauer et al., 2015 ; Heylens, Verroken et al., 2014 ; McDowell et al., 2020 ).…”
Section: Chapter 18 Mental Healthmentioning
confidence: 99%
“…Of note, several confounding factors co-occur with the presence of a GSA (e.g., larger schools, more experienced teachers; Baams et al, 2018). Additionally, state-level policies banning insurance policies from gender-based discrimination were associated with decreased suicidality in transgender and genderdiverse people (McDowell et al, 2020). Finally, indicating the importance of federal, LGBTQIA+-affirming policies, same-sex marriage policies have been associated with an estimated 134,446 fewer suicide attempts per year among high school students, with this effect driven by LGBQ+ students (Raifman et al, 2017).…”
Section: Structural-level Interventionsmentioning
confidence: 99%